Virtual Teaching in Confinement due to Covid-19. Case of the Faculty of Agricultural Economics of the Agrarian University of Ecuador - Victor Quinde Rosales; Rina Bucaram-Leverone; Martha Bucaram Leverone; María José Pincay López (Migration Letters, 2023)
With the purpose of encouraging research related to the economic, social, technological and health aspects of education, we present quantitative data from the teachers of the Faculty of Agricultural Economics of the Agrarian University of Ecuador, in order to learn about factors that intervened in the virtual teaching modality, in confinement by COVID-19. The survey format originally consisted of 49 questions containing educational, technological, health and economic data. A Principal Component Analysis (PCA) was performed, resulting in 11 components, with a cumulative percentage of 72.948, of which 7 were related among the variables (Discontinuity of virtual classes, Food budget, Labor distinction by gender, Health, Monthly expenditure, Virtual teaching, Use of virtual platforms), reflecting positive and negative factors of this modality, such as the easy adaptation of teachers to the platform, fuel savings by not moving to the institution, openness to the capacity of students on a platform. However, there are problems such as power failures, new internet service contracting, lack of commitment and student participation and above all the lack of contact between teacher and student.